2016
DOI: 10.3109/00365513.2015.1126854
|View full text |Cite
|
Sign up to set email alerts
|

Can admission serum cystatin C level be an early marker subclinical acute kidney injury in critical care patients?

Abstract: In this cohort of patients, a high sCys-C level at admission was found to be a predictor of subclinical AKI arising during their ICU stay. If supported with further studies, it might be used to provide more accurate and earlier knowledge about renal dysfunction and to take appropriate preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Thirty studies161718192021222324252627282930313233343536373839404142434445 finally met the inclusion criteria via full-text evaluation from 156 potentially eligible citations. Seven studies21222324252627 were selected from the previous meta-analysis (Zhang, et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty studies161718192021222324252627282930313233343536373839404142434445 finally met the inclusion criteria via full-text evaluation from 156 potentially eligible citations. Seven studies21222324252627 were selected from the previous meta-analysis (Zhang, et al .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies21222324252627 were selected from the previous meta-analysis (Zhang, et al . 2011)15 and an additional 23 studies1617181920282930313233343536373839404142434445 were complemented in the present meta-analysis. A flow chart of the identification and selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with accumulating evidence, conflicting results have raised. Gaygısız et al [27] and Martensson et al [28] found that the predictive value (AUC) of sCyC was 0.67, with low sensitivity and specificity. In the present study, we found that a 30% increase in sCyC was highly accurate in diagnosing CSA-AKI, with AUC 0.843 (75% sensitivity and 80% specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in accordance with these new findings, SCysC has been proposed as a filtration marker of GFR to replace SCr. Many studies [ 8 11 ] recently demonstrated that SCysC is a more sensitive serum marker than SCr for evaluating renal glomerular filtration function damage; however, there are some differing points of view [ 12 ]. To the best of our knowledge, only Van Pottelbergh, et al [ 13 ] completed a systematic review in 2010 that tried to investigate and ascertain the best process to provide measurements of renal function.…”
Section: Introductionmentioning
confidence: 99%